Analysis of Work Motivation, Work Discipline and Organizational Culture on Employee Performance at the Secretariat of the DPRD of North Sumatera Utara - Affny, Khailla Nazwa; Setiawan, Abdi (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of work motivation, work discipline, and organizational culture on employee performance at the Secretariat of the Regional House of Representatives (DPRD) of North Sumatra Province. This research employs a quantitative approach using an associative method. The population as well as the sample consists of all employees totaling 55 respondents, selected using a total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results of the partial test (t-test) indicate that work motivation has a positive and significant effect on employee performance, with a t-value of 14.161 greater than the t-table value of 1.675 and a significance level of 0.000 < 0.05. Work discipline also has a positive and significant effect on employee performance, with a t-value of 16.525 > 1.675 and a significance value of 0.000 < 0.05. Furthermore, organizational culture has a positive and significant effect on employee performance, with a t-value of 2.091 > 1.675 and a significance value of 0.041 < 0.05. The simultaneous test (F-test) shows that the F-value of 225.831 is greater than the F-table value of 2.73 with a significance level of 0.000 < 0.05, indicating that the three independent variables jointly have a significant effect on employee performance. The Adjusted R Square value of 0.926 indicates that 92.6% of the variation in employee performance is explained by work motivation, work discipline, and organizational culture, while the remaining 7.4% is influenced by other factors outside the research model.